Climate Factors Play a Limited Role for Past Adaptation Strategies in West Africa - Mertz, Ole; Mbow, Cheikh; Nielsen, Jonas Østergaard; Maïga, Abdou; Diallo, Drissa; Reenberg, Anette; Diouf, Awa; Barbier, Bruno; Moussa, Ibrahim Bouzou; Zorom, Malicki; Ouattara, Ibrahim; Dabi, Daniel (Ecology and society, 2010)
The Sudano-Sahelian zone of West Africa has experienced recurrent droughts since the mid-1970s and today there is considerable concern for how this region will be able to adapt to future climate change.To develop well targeted adaptation strategies, the relative importance of climate factors as drivers of land use and livelihood change need to be better understood.Based on the perceptions of 1249 households in five countries across an annual rainfall gradient of 400-900 mm, we provide an estimate of the relative weight of climate factors as drivers of changes in rural households during the past 20 years.Climate factors, mainly inadequate rainfall, are perceived by 30-50% of households to be a cause of decreasing rainfed crop production, whereas a wide range of other factors explains the remaining 50-70%.Climate factors are much less important for decreasing livestock production and pasture areas.Increases in pasture are also observed and caused by improved tenure in the driest zone.Adaptation strategies to declining crop production include 'prayer' and migration in the 400-500 mm zone; reforestation, migration, and government support in the 500-700 mm zone; and soil improvement in the 700-900 mm zone.Declining livestock holdings are countered by improved fodder resources and veterinary services.It is concluded that although rainfed crop production is mainly constrained by climate factors, livestock and pasture are less climate sensitive in all rainfall zones.This needs to be reflected in national adaptation strategies in the region.
openalex: W2289777700 mag: 2289777700
Keywords: openalex:import